2021
DOI: 10.1101/2021.07.12.21260409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding COVID-19 vaccine hesitancy in Pakistan: The paradigm of Confidence, Convenience, and Complacency; A Cross-sectional study

Abstract: Background and objectives: Vaccine hesitancy is a big obstacle for vaccination programs, as is anticipated for the COVID-19 vaccination program, resulting in low uptake of vaccines thereby hindering the process of reaching herd immunity. Bearing this in mind the current study was aimed to explore the determinants of vaccine hesitancy amongst the Pakistani population. Methodology: A cross-sectional study was carried out from the 23rd-31st January 2021. The conceptual framework of the study was based on the 3Cs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…However, despite the serious pandemic situation, the willingness of the Egyptian people to receive a vaccine against COVID-19 is still unclear. Vaccine hesitancy is a significant barrier to vaccination campaigns, as it obstructs the process of achieving herd immunity [8]. The initial strategy used by most countries worldwide was reducing disease transmission by mask policies, social distancing, hand sanitization, travel restrictions, and lockdowns [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the serious pandemic situation, the willingness of the Egyptian people to receive a vaccine against COVID-19 is still unclear. Vaccine hesitancy is a significant barrier to vaccination campaigns, as it obstructs the process of achieving herd immunity [8]. The initial strategy used by most countries worldwide was reducing disease transmission by mask policies, social distancing, hand sanitization, travel restrictions, and lockdowns [9].…”
Section: Introductionmentioning
confidence: 99%
“…The present study reported these factors to be responsible for vaccine hesitancy in Pakistan. Other factors highlighted by the present study that contributes to COVID-19 vaccine hesitancy among people include the perceived side effects of the COVID-19 vaccine [15,24,38,52,53,[60][61][62], concerns of people regarding different types of vaccines developed in a short period of time [58,60], and their alleged side effects including increased chances of death. People also reported some structural barriers, such as time constraint and facility accessibility issues [19,48].…”
Section: Discussionmentioning
confidence: 85%
“…This study found that people believed in the emergence of Islamophobia in the West, due to which they perceived the COVID-19 infection as well as the vaccination campaign as a genocidal attempt towards Muslims to control their population by causing infertility and considering it a "Western plot" in general, as is perceived about other vaccination campaigns by some communities in Pakistan [9][10][11]. Additionally, the prevalence of other myths and misconceptions included considering COVID-19 to be a man-made virus [18,57], fear of insertion of a secret micro-chip under the guise of vaccination [18], increased chances of death, and a lack of trust in the government [40], health workers [50], and the vaccine [24,39,42,47,51,[58][59][60]. The present study reported these factors to be responsible for vaccine hesitancy in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another study conducted to understand the COVID-19 vaccine hesitancy in Pakistan revealed that 50.6% of people are hesitant to take the COVID-19 vaccine, owing to the belief that the vaccine can cause various side effects like autism, infertility, autoimmune disorders, and death. 12 Various conspiracy theories against the COVID-19 vaccine are currently being spread in Pakistan. Fake narratives have been spread that the virus was invented to target Islamic nations so that Jews can rule the world.…”
Section: Factors Affecting Acceptance Of the Vaccinementioning
confidence: 99%
“…11 Another study conducted to understand the COVID-19 vaccine hesitancy in Pakistan revealed that 50.6% of people are hesitant to take the COVID-19 vaccine, owing to the belief that the vaccine can cause various side effects like autism, infertility, autoimmune disorders, and death. 12…”
Section: Factors Affecting Acceptance Of the Vaccinementioning
confidence: 99%